2003
DOI: 10.1289/ehp.5463
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polychlorinated biphenyl levels across studies of human neurodevelopment.

Abstract: Polychlorinated biphenyls (PCBs) are persistent pollutants that are ubiquitous in the food chain, and detectable amounts are in the blood of almost every person in most populations that have been examined. Extensive evidence from animal studies shows that PCBs are neurotoxins, even at low doses. Interpretation of human data regarding low-level, early-life PCB exposure and subsequent neurodevelopment is problematic because levels of exposure were not similarly quantified across studies. We expressed the exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
161
14

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(195 citation statements)
references
References 39 publications
20
161
14
Order By: Relevance
“…The PCB concentrations are in agreement with previous reports from the Faroese population (25,31), and these PCB concentrations are high compared to international data on human levels of PCBs (51). The concentrations are comparable to serum levels of PCBs in Eastern Slovakia, where a hotspot is located (52).…”
Section: Discussionsupporting
confidence: 90%
“…The PCB concentrations are in agreement with previous reports from the Faroese population (25,31), and these PCB concentrations are high compared to international data on human levels of PCBs (51). The concentrations are comparable to serum levels of PCBs in Eastern Slovakia, where a hotspot is located (52).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, environmental chemicals that can produce TH insufficiency or interfere with TH signaling during development are likely to alter important developmental events (Zoeller et al, 2002). Recent epidemiologic studies have indicated the significant relationships between circulating levels of TH and exposure to environmental chemicals (Blount et al, 2006;Longnecker et al, 2003). Thus, understanding the action of environmental chemicals that can interfere with TH signaling is highly important to human health.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to behaviour, gender-specific tools should be considered, if not implemented. Both DES and PCB exposures have been associated with alterations in gender-specific behaviour (Collaer & Hines, 1995;Guo et al, 1995;Longnecker et al, 2003). Standardized clinical assessments are available for newborns and paediatric populations, which can be tailored to meet particular research goals, taking into account the characteristics or physical/ biological properties of the exposure under investigation.…”
Section: Human Studiesmentioning
confidence: 99%